Maternal diabetes disrupts early corticogenesis through altered mitotic gene regulation: a transcriptomic analysis - Valle-Bautista, Rocío; de la Merced-García, Diana S.; Díaz-Piña, Dafne A.; Díaz, Néstor Fabián; Ávila-González, Daniela; Molina-Hernández, Anayansi (Frontiers in Endocrinology, 2025)
Maternal diabetes is linked to neurodevelopmental impairments in offspring, but the underlying molecular mechanisms remain unclear. Early cortical neurogenesis is a critical window vulnerable to maternal metabolic disturbances. Here, we analyzed global gene expression by RNA sequencing in dorsal prosencephalon tissue from 12-day-old embryos without neural tube defects. Gene ontology (GO) enrichment identified key candidates, validated by qRT-PCR, Western blotting, and immunofluorescence. We found 247 differentially expressed genes (111 upregulated, 136 downregulated), with upregulated genes enriched in mitosis, microtubule organization, and chromosome segregation pathways. Aurkb and Numa1 emerged as central regulators and were confirmed upregulated by qRT-PCR. Although Western blotting showed no protein-level changes, immunofluorescence revealed altered subcellular localization, disrupted spindle architecture, monopolar spindles, and increased asymmetric divisions in neural stem cells. These results suggest maternal diabetes disrupts mitotic regulation, accelerates neurogenic differentiation, and depletes the neural stem cell pool, potentially contributing to cortical defects and neurodevelopmental impairments in offspring. This study provides new insight into the developmental origins of neurodevelopmental disorders in the context of maternal diabetes, highlighting mitotic dysregulation as a potential mechanistic link in fetal programming.